2018
DOI: 10.1108/bpmj-09-2017-0241
|View full text |Cite
|
Sign up to set email alerts
|

Designing complex socio-technical process systems – the airport example

Abstract: Purpose A configurable reference model can be used to assist in the development and management of business processes in complex, multi-stakeholder environments. The purpose of this paper is to demonstrate a process design in such environments via configurable process reference modelling, using airports as an example. Design/methodology/approach Existing reference modelling methods around process modelling, merging and configuration are extended to include contextual and spatial factors using the design scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…The airline companies are responsible for offloading aircraft; immigration entrances are the personalized border protection services (Irandu, 2018). All these units socialize in the airport to promote the risk-free, successful, and protected services for passengers (Abeyratne, 2017;Mazhar et al, 2019). This enables airport managers to embrace effective methods to enhance airport service quality and achieve excellent customer satisfaction and engagement (Pitchforth et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The airline companies are responsible for offloading aircraft; immigration entrances are the personalized border protection services (Irandu, 2018). All these units socialize in the airport to promote the risk-free, successful, and protected services for passengers (Abeyratne, 2017;Mazhar et al, 2019). This enables airport managers to embrace effective methods to enhance airport service quality and achieve excellent customer satisfaction and engagement (Pitchforth et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a dynamic perspective of architectural implementation, the transformation from the current state to the target state is determined by solution design. However, in most cases, the entire design and implementation is performed in a cross-functional project (Czarnecki and Dietze, 2017;Leyh et al, 2017;Mazhar et al, 2018), where there is always a gap between the initial "intended" scope and the present-day EA scope in practice. Research (Bernus et al, 2016;Mazhar et al, 2018) has revealed that the EA scope no longer necessarily involves a single element, but rather a socio-technical system.…”
Section: Related Workmentioning
confidence: 99%
“…However, in most cases, the entire design and implementation is performed in a cross-functional project (Czarnecki and Dietze, 2017;Leyh et al, 2017;Mazhar et al, 2018), where there is always a gap between the initial "intended" scope and the present-day EA scope in practice. Research (Bernus et al, 2016;Mazhar et al, 2018) has revealed that the EA scope no longer necessarily involves a single element, but rather a socio-technical system. EA frameworks should be considered from related business, economic, social, and ecological perspectives (Bernus et al, 2016), such that they can represent the stakeholder's specific concerns.…”
Section: Related Workmentioning
confidence: 99%